2012
DOI: 10.1634/theoncologist.2012-0044
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Sunitinib for the Treatment of Progressive Well-Differentiated Locally Advanced or Metastatic Pancreatic Neuroendocrine Tumors

Abstract: On May 20, 2011, the U.S. Food and Drug Administration (FDA) approved sunitinib malate capsules (Sutent; Pfizer, Inc., New York) for the treatment of progressive, well-differentiated pancreatic neuroendocrine tumors (pNETs) in patients with unresectable locally advanced or metastatic disease. In a phase III randomized trial, 171 patients received either sunitinib (37.5 mg) or placebo once daily. The progression-free survival (PFS) interval was the primary efficacy endpoint. Secondary endpoints included the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 12 publications
0
88
0
Order By: Relevance
“…Sunitinib was approved by the EMA in 2010 and the FDA in 2011 for the treatment of patients with progressive, unresectable, or recurrent/metastatic, well-differentiated panNETs [7,8]. Due to the early termination of the phase III study, the phase IV study reported here was conducted to provide additional information in this population, and to meet regulatory post-approval commitments to confirm the efficacy and safety of sunitinib in advanced/metastatic, well-differentiated, unresectable panNETs.…”
Section: Introductionmentioning
confidence: 99%
“…Sunitinib was approved by the EMA in 2010 and the FDA in 2011 for the treatment of patients with progressive, unresectable, or recurrent/metastatic, well-differentiated panNETs [7,8]. Due to the early termination of the phase III study, the phase IV study reported here was conducted to provide additional information in this population, and to meet regulatory post-approval commitments to confirm the efficacy and safety of sunitinib in advanced/metastatic, well-differentiated, unresectable panNETs.…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosine kinase inhibitors (TKIs) such as sunitinib (Sutent; Pfizer, New York, New York, USA) and sorafenib (Nexavar; Bayer, Leverkusen, Germany) directly inhibit the vascular endothelium growth factor (VEGF) receptors and other receptors involved in angiogenesis. Sunitinib is proposed as a first-line treatment in metastatic renal cell carcinoma and as a second-line treatment in gastrointestinal stromal tumors (GISTs) and pancreatic neuroendocrine tumor; sorafenib, is proposed as a first-line treatment in hepatocellular carcinoma and as a second-line treatment in metastatic clear carcinoma of the kidney and metastatic thyroid cancer [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The initial OS analysis, based on 18% of events, suggested an OS benefit for the sunitinib group (HR for death was 0.41 [95% CI: 0.19-0.89; p = 0.02]). However, further analysis based on 43% of the events did not show a statistically significant difference between the two groups (HR: 0.74 [0.47-1.17]) [60]. It has been suggested that the early unplanned efficacy assessment may have resulted in an overestimation of the PFS magnitude.…”
Section: Considerations That Need To Be Taken Into Account When Choosmentioning
confidence: 94%
“…It has been suggested that the early unplanned efficacy assessment may have resulted in an overestimation of the PFS magnitude. The FDA recommended that such practice should be discouraged as unplanned early analyses, with subjective end points such as PFS, can increase the risk of identifying an erroneous false positive result, thereby leading to a type I error and overestimating the treatment effect of the experimental agent [60].…”
Section: Considerations That Need To Be Taken Into Account When Choosmentioning
confidence: 99%